Violence, visual culture, and the black male body - Jackson, Cassandra, 1972- (Routledge research in cultural and media studies ;, 2011)
From early photographs of disfigured slaves to contemporary representations of bullet-riddled rappers, images of wounded black men have long permeated American culture. While scholars have fittingly focused on the ever-present figure of the hypermasculine black male, little consideration has been paid to the wounded black man as a persistent cultural figure. This book considers images of wounded black men on various stages, including early photography, contemporary art, hip hop, and new media. Focusing primarily on photographic images, Jackson explores the wound as a specular moment that media.